Form and Structure of Kentrung Art in Ngasem Village Batealit District Jepara Regency - Harwanto, Dody Candra; Sunarto, Sunarto (Catharsis, 2018)
Kentrung art is a folk theater art that tells a story in the form of prose and interspersed by pantun, an Indonesian unique form of prose. It is played by sung, and uses musical instrument called Ã¢â‚¬Å“TerbangÃ¢â‚¬Â or Rebana. This research aims to analyze the shape and structure of Kentrung art in Ngasem Village District Batealit Jepara regency. The method used in this research is qualitative descriptive with interpretative case study research design. The research data was collected by observation technique, interview, and documentation study. It is also using triangulation techniques of sources and data to maintain its validity. Meanwhile, the data analysis technique is done through the process of reduction, presentation, and withdrawal of conclusion (verification). The results of this study indicate that, Kentrung musical form consists of two elements, namely elements of time and melody. The time element of Kentrung art employs Allegreto tempo which means fast or between the speed limit of 104-112 steps per minute; the meter uses 4/4, meaning there are four or four minutes of beats on each bar; and rhythmic patterns are divided into two types (senggakan and sautan) which generally use the value of half-tap, and on the big fly using the pattern of rhythm singkup. Most melodies use a half-tap note with the highest tone of G# 5 (la), and the lowest tone is F# 4 (sol). Meanwhile, the musical structure of Kentrung consists of two sentences or periods namely repeated A B.